Pengaruh Aplikasi Tooth Mousse Terhadap KekasaranPermukaan Resin Komposit Nanofil Yang DirendamDalam Minuman Berkarbonasi - Nathalia, Nency Adella, Drg. Noor Hafida Widiastuti, Sp. KG (2017)
The nanofill composite resin is a nanoparticle dental restoration material which has mechanical strength and a good polish resistance. The weakness of the nanofill composite resin is porosity and can absorbs liquid such as carbonated beverages. Consumption of carbonated beverages causes acidic conditions in the oral cavity so that can affect to enamel or restoration roughness. Tooth mousse has contain casein which interact with calcium and phosphate or known as CPPACP which can reduce erosion and increase the micro hardness of email and prevent demineralization. This study aimed to know the effect of tooth mousse application to nanofil composite resin roughness in carbonated beverage immersion. This study uses 32 samples divided into 2 groups, group A nanofil composite resin with tooth mousse application and group B without tooth mousse application. The two groups which had measured for initial roughness, then immersed in carbonated beverage and tested the final roughness using surface roughness tester. Data were tested using Shapiro-Wilk test (p>0.05), Levene's test (p>0.05) and Independent T-test (p<0.05). The results showed that groups with tooth mousse applications had a lower roughness value than those with no tooth mousse application.